Globalization, technology and the transnational capitalist class. Issue 2 (13th April 2015) - Harris, Jerry
Abstract : Purpose: – The purpose of this paper is to explore how capitalism has developed into a deeply integrative economic system of financial investments and manufacturing. This process of globalization has brought about the emergence of a transnational capitalist class that rules the world's economy. Financialization, created by the speed and interconnectivity of information technologies, is a key element that has produced immense wealth for a few while reducing their dependence on the labor of workers. This system of global accumulation has lead to a crisis of democracy with several different possible outcomes. Design/methodology/approach: – This paper begins with an historical examination of capitalism and capitalist class formation by tracing developments from nation-centric capitalism to globalization. A conceptual explanation of the development of the transnational capitalist class (TCC) is offered. Research on current economic data to support the thesis on the emergence of the TCC in both its private and statist forms is included, as well as an examination of the latest technology developments that affect financialization and how this impacts class relations. The conclusion analyzes the development of democracy as a class dialectic, and the impact of globalization that is altering the historic relationships between capital and labor. The paper ends with a discussion of possible political/economic futures. Findings: – Globalization is a new era in which capitalism has deepened its inherent tendency toward creating world markets and production. This process has been greatly enhanced by the new technological tools of financial production. Organizing and overseeing this system of global accumulation is the transnational capitalist class. The emergence of this class has transformed class relations based within the historic perimeters of nation-states, and it threatens the content and character of democracy that arose out of the bourgeois democratic revolutions in America and France. Originality/value: – Transnational Capitalist Class Theory is a recently developed field of research. It is a new critic of mainstream international relations analysis which centers on nation to nation relationships. It also differs with world system theory which divides countries into a center/peripheral analysis. Within the field of TCC research, this paper offers an original historic perspective between global economics and the development of democracy. It also makes new theoretical connections between information technology, financialization and the destruction of the social contract.